Optimizing the Provision of PBB Billing Letters to Increase Local Revenue at Bapenda UPTB 2 Rungkut Region in Dukuh Sutorejo Village - Mukti, Nilam Indra Permata; Imaningsih, Niniek; Fadil, Cholid (Unram Journal of Community Service, 2025)
Optimizing Property Tax (PBB) revenue is a primary focus in enhancing the Regional Original Revenue (PAD) in Surabaya City. This study aims to analyze the implementation of PBB tax bill delivery through a door to door approach in Dukuh Sutorejo Village, Mulyorejo District. The methods used include tax arrears data verification, field validation, and uploading collection results into the Regional Revenue Agency (Bapenda) system. The data were analyzed to identify obstacles to PBB payments, such as discrepancies in Tax Object Numbers (NOP), taxpayers' economic constraints, and a lack of tax awareness. Its results indicate that delivering PBB tax bills directly increases tax payment realization, both through full payment and installment methods. Additionally, field validation successfully identified NOPs that require updates or deletion, thereby improving the efficiency of the tax collection process. Education provided during verification effectively raised taxpayers' awareness of the importance of tax compliance. The conclusion of this study is that the door to door approach, combined with the delivery of PBB tax bills, can be a strategic solution to optimize regional tax revenue. This method is recommended for broader implementation to support sustainable regional development through increased Regional Original Revenue (PAD).